2015
DOI: 10.1016/j.seizure.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association study of the HLA class II alleles DRB1, DQA1, and DQB1 in patients with pharmacoresistant temporal lobe epilepsy associated with mesial hippocampal sclerosis

Abstract: The allele HLA DRB1*13:02 has exhibited a tendency to behave as a susceptibility factor for TLE-HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The results showed a significantly high frequency of HLA‐DQ2, HLA‐DR4, and HLA‐DR7 in this population. However, a 2015 Brazilian study failed to demonstrate any association with HLA types in the Brazilian MTLE‐HS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a significantly high frequency of HLA‐DQ2, HLA‐DR4, and HLA‐DR7 in this population. However, a 2015 Brazilian study failed to demonstrate any association with HLA types in the Brazilian MTLE‐HS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sample size is limited, our findings may suggest that a high frequency of HLA-DRB1*13 allele plays a role in the induction of hyperexcitability of the epileptic tissue. Recently, the HLA-DRB1*13:02 allele was found to be elevated in patients with MTLE-HS in comparison with controls, although the statistical significance was lost after Bonferroni correction (43). These findings may be taken into consideration as further evidence for immune-dependent genetic factors in the etiology of HS.…”
Section: Evaluation Of Cytokinesmentioning
confidence: 93%
“…98 In Asian from China and Malaysia, an association of CBZ-induced Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (SJS/TEN) with the HLA-B*1502 polymorphism has been demonstrated. 99,100 In another population with ancestral European and Japanese lineages, the HLA-A*1301 allele presented an association with drug resistance to CBZ92. 99 Other studies have attempted to identify a relationship between polymorphisms of inflammatory molecules and the development of DRE, but the results are controversial or questionable, since no other similar studies have been reported in these or other populations.…”
Section: Neuroinflammation and Bloodbrain Barrier Dysfunction In Drug...mentioning
confidence: 99%
“… 98 In Asian populations from China and Malaysia, an association of CBZ‐induced Stevens‐Johnson syndrome (SJS) and toxic epidermal necrolysis (SJS/TEN) with the HLA‐B*1502 polymorphism has been demonstrated. 99 , 100 In another population with ancestral European and Japanese lineages, the HLA‐A*1301 allele presented an association with drug resistance to CBZ92. 99 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation